Educator insights: a need analysis on developing mobile applications as learning interventions for Dyscalculia - Mahat, Jazihan; Syed Abdullah, Sharifah Intan Sharina; Mohd Ayub, Ahmad Fauzi; Hashim, Noor Hasanah (Macrothink Institute, 2025)
Dyscalculia, a specific learning disability affecting mathematical abilities, presents challenges in educational settings. This study investigates the academic needs of students with learning disabilities, specifically Dyscalculia, and explores effective interventions to enhance their learning experiences. Semi-structured interviews with experienced educators were conducted using a qualitative approach to gather insights into teaching these students. The findings emphasize the importance of mastering foundational mathematical concepts, such as numbers 1 to 10, for further understanding. Key themes include the need for tailored learning approaches and technology integration in teaching practices. The research highlights the potential of mobile applications as tools to boost engagement and comprehension. While this study offers valuable insights, it acknowledges limitations such as the small sample size and calls for broader research across diverse educational settings. This article aims to guide educators and policymakers toward inclusive, effective mobile learning interventions for those who are either at risk of or have already been diagnosed with learning disabilities, specifically Dyscalculia.